Potensi dan Prospek Wisata Halal Dalam Meningkatkan Ekonomi Daerah (Studi Kasus: Nusa Tenggara Barat) - Subarkah, Alwafi Ridho (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2018)
This study discusses halal tourism as an instrument of Indonesian public diplomacy to increase tourist visits and improve regional economics, because large halal tourism potential is expected to have an influence on the regional economy, especially for West Nusa Tenggara Province as a halal tourist destination. This study uses qualitative research with the concept of public diplomacy and halal tourism concepts. The results of this study indicate that Indonesian public diplomacy by presenting itself as a halal tourist destination is considered successful can attract foreign tourists, especially Muslim tourists and attract investment, as well as the development of halal tourism also has a positive increase, so that increased tourist visits and investments can be used to improve the economy areas such as West Nusa Tenggara as halal tourist destinations.